Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Answer:
(4,1)
Step-by-step explanation:
Multiply the first equation by -3
(x-5=-y)*-3 = -3x+15=3y
Then combine like terms with the new equation and the second equation
(-3x+15=3y) + (3x-10=2y) = 5=5y
Divide 5 by both sides
1=y
Plug in 1 for y in an equation. Doesn’t matter which one and solve
x-5=-(1)
Distribute the negative sign to the 1
x-5=-1
Add 5 to both sides
x=4
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.